Toxic epidermal necrosis associated with afatinib: A case report and literature review - Yang, Wei; Lu, Yansong; Wu, Ze; Niu, Jun (Frontiers in Oncology, 2023)
Objective: Afatinib is the first-line treatment for patients with metastatic non-small cell lung cancer (NSCLC). The main adverse drug reactions are diarrhoea, rash or acne, stomatitis and paronychia. Methods: We report a case who received afatinib and developed toxic epidermal necrosis (TEN). The culprit drug was ascertained using the algorithm of drug causality for epidermal necrolysis (ALDEN). Combining the previous literature reports, we analyzed the clinical characteristics, treatment regimens and therapy outcomes of patients. Results: Most Stevens-Johnson syndrome/ Stevens-Johnson syndrome-toxic epidermal necrolysis overlap associated with afatinib had a latency period over thirty days. Therapy with corticosteroids resulted in significant improvement of clinical symptoms, and led to a complete remission. Conclusion: Most of severe cutaneous adverse reactions induced by afatinib have a longer incubation period, and patients must be monitored closely during afatinib treatment.